Knowledge and perception of roman catholic mothers towards natural family planning methods at Kawale Health Centre - Chirwa, Regan, Redson (Kamuzu University of Health Sciences, 2022)
This study will be conducted to explore the knowledge and perception that Roman Catholic 1 mothers have towards the use of Natural Family Planning methods. Specifically the areas of interest are: to assess knowledge and perceptions they have on Natural and Artificial Family 1 planning methods, what they know about their church's stand on artificial and natural family planning methods.